The Development of Traditionalist and Conservative Schools of Thought and Their Relevance to Twenty-First-Century Islamic Education - Rafika Nisa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Traditionalism and conservatism have a complex relationship within the context of Islamic educational thought in the twenty-first century. Traditionalism provides a foundation for religious values and ethical principles, while conservatism plays an important role in preserving religious identity and heritage. However, both perspectives may also hinder intellectual progress and limit the ability to respond effectively to the challenges of the modern era. Contemporary Islamic educational thought therefore requires a balanced integration of traditionalism and conservatism with modern perspectives and adaptation to the demands of globalization. Such integration can be achieved by promoting educational innovation that addresses the diverse needs of younger generations while remaining open to new ideas. In addition, Islamic education should adopt a flexible approach to understanding and implementing religious teachings, enabling it to adapt to social change and contemporary challenges. At the same time, it should foster critical thinking toward religious teachings and traditions while encouraging constructive engagement with modern thought to provide relevant solutions to emerging issues. This balanced approach is expected to strengthen the relevance and sustainability of Islamic education in the twenty-first century.